Empowering Elementary School Teachers through the Integration of Education for Sustainable Development (ESD) into the National Curriculum to Create Sustainable Schools - Ricky Setiawan; Wulan Patria Saroinsong; Sujarwanto Sujarwanto; Zeni Zakia Zamania; Rifka Anisa Ummami; Moch. Naufal; Zinni Akmalia (Universitas Negeri Surabaya, 2026)
ESD (Education for Sustainable Development) is oneof the important approaches in realizing 21st century learning that isoriented towards sustainability. However, teachers at SD Labschool 2 UNESA still have limited understanding of integrating the concept of ESD into thenational curriculum. In addition, the unavailability of implementation guidelines andsystematic learning resources has resulted in suboptimal sustainability-based learning practices. Objective: This program aims to empower teachers in education management through the integration of Education for Sustainable Development (ESD) into the elementary school curriculum and the development of the ESD Connect platform as a collaborative tool to connect sustainable learning practices in schools. Methods: The method used in this study was the Project Action Plan (PAP), which was divided into three stages: (1) the preparation stage, (2) the implementation stage, and (3) the monitoring stage. Results: Based on the test results, the success rate for website creation was 100%, the participant attendance rate for the training was 86.67%, and the material delivery rate was 100%. Furthermore, based on observations, participants' ability to understand the material and fill in web content was considered good.Conclusion: These results show that the service program has been able to improve participants' ability to share and adopt best practices from other schools in sustainable education. Keywords: Teacher Empowerment; Education for Sustainable Development (ESD); National Curriculum.